2021
DOI: 10.3390/cancers13122936
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Human Hsc70 System by Small Ligands as a Potential Anticancer Approach

Abstract: Heat shock protein (Hsp) synthesis is upregulated in a wide range of cancers to provide the appropriate environment for tumor progression. The Hsp110 and Hsp70 families have been associated to cancer cell survival and resistance to chemotherapy. In this study, we explore the strategy of drug repurposing to find new Hsp70 and Hsp110 inhibitors that display toxicity against melanoma cancer cells. We found that the hits discovered using Apg2, a human representative of the Hsp110 family, as the initial target bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 121 publications
(148 reference statements)
0
10
0
Order By: Relevance
“…Thus, the repurposing of drugs appears promising and is not a one-way road. As far as drug repurposing is concerned, the disinfectant hexachlorophene ( 20 ) and the spasmolytic drug pinaverium bromide ( 4 ) are further interesting examples of Hsp70 inhibitory activity [ 50 , 82 ]. In contrast to the cationic mitochondria-targeting compounds with preference for mortalin binding, the anionic ruthenium complex 22 (KP1339) is an efficient Grp78 suppressor [ 85 , 86 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the repurposing of drugs appears promising and is not a one-way road. As far as drug repurposing is concerned, the disinfectant hexachlorophene ( 20 ) and the spasmolytic drug pinaverium bromide ( 4 ) are further interesting examples of Hsp70 inhibitory activity [ 50 , 82 ]. In contrast to the cationic mitochondria-targeting compounds with preference for mortalin binding, the anionic ruthenium complex 22 (KP1339) is an efficient Grp78 suppressor [ 85 , 86 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compound 4 inhibited cell proliferation (IC 50 of ca. 10 µM) of A2058 melanoma cells and induced apoptosis in these cells [ 50 ]. Its binding site was located at the NBD and linker domains of Hsc70.…”
Section: Hsp70 Inhibitorsmentioning
confidence: 99%
“…A 70 kDa heat-shock cognate protein (HSC70/HSPA8) is a molecular chaperone that plays an essential role in cell survival [35,36]. HSC70 is a member of the heat-shock protein 70 family of proteins involved in protein folding, translocation or sorting, and regulation of signaling in cells [37]. It has been reported that the complex of HSC70 and MSG1 promotes Smad3-mediated transcription by enhancing coactivators [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, no inhibitors have been reported for any fungal Hsp110s. In fact, it has been challenging to develop modulators for Hsp110s in general due to a limited understanding of the molecular mechanisms of their chaperone activity, although inhibiting Hsp110s has been established as a potentially effective strategy against cancers 26 28 . To date, only one specific small molecule inhibitor has been reported for Hsp110s 29 , and this inhibitor is a competitor of ATP for a human Hsp110, which raises questions regarding specificity.…”
Section: Introductionmentioning
confidence: 99%